Evidence‐based practice improves patient outcomes and healthcare system return on investment: Findings from a scoping review. Issue 1 (8th February 2023) - Connor, Linda; Dean, Jennifer; McNett, Molly; Tydings, Donna M.; Shrout, Amanda; Gorsuch, Penelope F.; Hole, Ashley; Moore, Laura; Brown, Roy; Melnyk, Bernadette Mazurek; Gallagher‐Ford, Lynn
Abstract: Background: Evidence‐based practice and decision‐making have been consistently linked to improved quality of care, patient safety, and many positive clinical outcomes in isolated reports throughout the literature. However, a comprehensive summary and review of the extent and type of evidence‐based practices (EBPs) and their associated outcomes across clinical settings are lacking. Aims: The purpose of this scoping review was to provide a thorough summary of published literature on the implementation of EBPs on patient outcomes in healthcare settings. Methods: A comprehensive librarian‐assisted search was done with three databases, and two reviewers independently performed title/abstract and full‐text reviews within a systematic review software system. Extraction was performed by the eight review team members. Results: Of 8537 articles included in the review, 636 (7.5%) met the inclusion criteria. Most articles (63.3%) were published in the United States, and 90% took place in the acute care setting. There was substantial heterogeneity in project definitions, designs, and outcomes. Various EBPs were implemented, with just over a third including some aspect of infection prevention, and most (91.2%) linked to reimbursement. Only 19% measured return on investment (ROI); 94% showed a positive ROI, and none showed a negative ROI. The two most reported outcomes were length of stay (15%), followed by mortality (12%). Linking Evidence to Action: Findings indicate that EBPs improve patient outcomes and ROI for healthcare systems. Coordinated and consistent use of established nomenclature and methods to evaluate EBP and patient outcomes are needed to effectively increase the growth and impact of EBP across care settings. Leaders, clinicians, publishers, and educators all have a professional responsibility related to improving the current state of EBP. Several key actions are needed to mitigate confusion around EBP and to help clinicians understand the differences between quality improvement, implementation science, EBP, and research.